2017
DOI: 10.1021/acsnano.7b01457
|View full text |Cite
|
Sign up to set email alerts
|

Broken Symmetry Induced Strong Nonlinear Optical Effects in Spiral WS2 Nanosheets

Abstract: Transition metal dichalcogenides (TMDs) have provided a fundamental stage to study light-matter interactions and optical applications at the atomic scale due to their ultrathin thickness and their appropriate band gap in the visible region. Here, we report the strong nonlinear optical effects, including second-harmonic generation (SHG) and third-harmonic generation (THG) in spiral WS structures. SHG intensity quadratically increases with layer numbers, other than diminishing the oscillation of 2H stacking TMDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
162
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(170 citation statements)
references
References 49 publications
6
162
0
2
Order By: Relevance
“…In addition, the two‐photon absorption response of WS 2 and WSe 2 films was also discovered, as shown in Figure d–f. Recently, more TMDCs including MS 2 , MSe 2 , MTe 2 , have been also deeply studied. These explorations lay a foundation for their applications in nonlinear photonics.…”
Section: Fundamental Of 2d Layered Materialsmentioning
confidence: 99%
“…In addition, the two‐photon absorption response of WS 2 and WSe 2 films was also discovered, as shown in Figure d–f. Recently, more TMDCs including MS 2 , MSe 2 , MTe 2 , have been also deeply studied. These explorations lay a foundation for their applications in nonlinear photonics.…”
Section: Fundamental Of 2d Layered Materialsmentioning
confidence: 99%
“…SHG of the bulk MoS 2 is very weak and χ (2) is around 10 −14 m/V; however, three groups simultaneously reported that SHG of monolayer MoS 2 , WS 2 , and WSe 2 increased dramatically . Later, numerous SHG studies were conducted on MoS 2 , WS 2 , WSe 2 , MoSe 2 , and MoTe 2 , and χ (2) was reported on the order of magnitude of 1 nm/V, which is much higher than the most used commercial nonlinear crystals (eg, χ (2) of BBO, KTP, and LiNbO 3 are on the order of magnitude of pm/V). The large nonlinear susceptibility of monolayer compared with bulk is ascribed to the inversion symmetry breaking.…”
Section: Nlo Processes In Tmdsmentioning
confidence: 99%
“…By fitting the 6‐fold pattern with the cos 2 (3 θ + φ 0 ) or sin 2 (3 θ + φ 0 ) function, φ 0 can be resolved and the initial orientation of the crystal can be determined. This polarization dependence was widely utilized to probe the crystal orientation of h‐BN and monolayer TMDs . Especially, it is useful for the heterostructure stacking where the initial orientation need to be resolved accurately .…”
Section: Nlo Processes In Tmdsmentioning
confidence: 99%
“…With the development of CVD technology, valley polarization contrast in artificial structures of multilayers TMDCs has been attracting considerable attention. One remarkable structure fabricated using this technology is the spiral nanostructure of TMDCs which has a screw morphology as shown in Figure 3b 96–98. Interestingly, transmission electron microscopy analysis revealed that this spiral nanostructure has an AB stacking structure, as shown in Figure 3c.…”
Section: Valley Excitons and Pseudospins In 2d Tmdcsmentioning
confidence: 97%
“…Inset shows the zoomed‐in atomic force microscope image of a spiral WS 2 nanosheet. Reproduced with permission 96. Copyright 2017, American Chemical Society.…”
Section: Valley Excitons and Pseudospins In 2d Tmdcsmentioning
confidence: 99%